Fostering creativity in the classroom. : Ecofeminist movies for a better future - Echegoyen Sanz, Yolanda; Martín-Ezpeleta, Antonio (Journal of Education Culture and Society, 2021)
Aim. The aim of this work is to present a qualitative analysis of the movie proposals prepared by preservice teachers in the context of an educational experience around the ecofeminist movement. The responses to a final questionnaire about sustainability awareness are also analysed.Methods. The participants were 47 alumni of the Grades of Early Childhood Education and Primary Education at a Spanish university. After a lecture about ecofeminism and reading a series of fragments of the young literature novel Yabarí by Lola Robles (2017), preservice teachers had to prepare the proposal for an ecofeminist movie, with a synopsis, plot, characters description, cast, and the script for a key scene. To assess the experience the students completed a questionnaire about different aspects of the proposal at the end of the semester, along with a validated questionnaire about sustainability awareness.Results and conclusion. The analysis of the ecofeminist movies prepared and the responses to the questionnaires shows how the students were able to assimilate the ecofeminist thesis and incorporate them to their reflection about sustainability. This is also manifested in the results of the “Attitudes toward Sustainable Development scale”, which indicate a high level of sustainability attitudes in these preservice teachers, with no differences between genders. The creativity of these preservice teachers is evident in the variety of approaches to the topic in the different movies proposed. We can conclude that the ecofeminist topic is relevant in the classroom because it contributes to enhancing the ethical debate and driving the teaching-learning process in an interdisciplinary manner, perfectly aligned with the objectives of the 2030 Agenda for sustainable development.